Does Smartphone Gaming have a Positive Effect on the Acquisition of Laparoscopic Skills? - Samuel Tan, Yon Xiang; Richelle, Chua; Aini Fahriza, Ibrahim; Clarence, Lei; Guan Chou, Teh (SCIENCE DOMAIN INTERNATIONAL, 2022)
Aims: Videogaming has been shown to have a positive effect on hand-eye co-ordination, improve visuo-spatial ability and improve cognitive flexibility. However, the majority of the literature examining the subject utilise gaming consoles where physical controllers are used to dictate on- screen movements. The current evidence examining the association between laparoscopic skills and smartphone or touch-based gaming is extremely limited. This study seeks to examine whether smartphone gaming has a positive effect on laparoscopic skill acquisition. Study Design: Prospective cohort study Place and Duration of Study: Department of Urology, Sarawak General Hospital, Kuching Sarawak between August 2020 and January 2021. Methodology: We included 74 medical students (26 male, 48 female, age range 22 – 24 years) without any prior exposure to either laparoscopy or surgery. Subjects were assigned to either Gamer or Non-Gamer groups based on a self-reported questionnaire. Formal testing of laparoscopic skills was undertaken via the Modified MISTELS (McGill Inanimate System for Training and Evaluation of Laparoscopic Skills) to establish a baseline. The Gamer group were then asked to play at least 30 minutes of a smartphone game for 21 days whilst the Non-Gamer group were asked to refrain from commencing any virtual games. Repeat assessment of laparoscopic skills was performed and scores between the 2 groups was compared using 2-tailed independent t-test. Results: In total 74 medical students completed the study with 34 in the Non-Gamer Group and 40 in the Gamer Group. There was no statistically significant difference between groups at baseline assessment. Following the intervention period, the Gaming Group performed significantly better than the Non-Gaming Group with a mean Overall score of 261.05 vs 154.99 (p<.001). Additionally, the Gaming group showed statistically significant higher scores in all three component tasks, with most marked difference in Intracorporeal Suturing. Conclusion: Smartphone gaming requiring the use of multi-action gestures improves the ability of novices to acquire laparoscopic skills compared to no exposure. The findings support the use of smartphone gaming to be used as an adjunct to laparoscopic training due to the convenience, portability and ease of access to most medical students and professionals.